Rethinking Early Marriages in Indonesia: Advocating for Reform to Tackle Domestic Conflict, Violence, and Rights Infringements - Utami, Ria Anggraeni; Pradityo, Randy; Karo, Lidia Br.; Karinda, Risna (Universitas Negeri Semarang, 2023)
The significance of establishing an age limit for marriage cannot be overstated, as marrying at a young age often leads to heightened domestic conflicts, encompassing instances of domestic violence and an increased likelihood of divorce. This study employs an empirical juridical research method, combining field research and library materials, to delve into the factors contributing to child marriages. The findings reveal various drivers of child marriages, notably rooted in economic hardships within families (poverty), parental-arranged marriages, influence from peer groups with a high prevalence of early marriages, cultural perspectives on marriage age, discontinued education, and instances of premarital sexual activities. The repercussions of child marriages extend beyond the act itself, jeopardizing fundamental rights that the young individuals may have otherwise enjoyed. This research underscores the vulnerability of several rights in the context of child marriages, including the right to education, the right to a sustainable livelihood, the right to holistic growth and development, and the right to live free from violence. The forms of violence stemming from child marriages are manifold, encompassing both physical and psychological abuse perpetrated by partners or individuals with familial ties, such as blood relations, marital bonds, and guardians residing in the household. Addressing these multifaceted factors is crucial for the protection and well-being of individuals ensnared in early marriages, paving the way for more informed policies and interventions.